Impact of docetaxel plus ramucirumab in a second‐line setting after chemoimmunotherapy in patients with non‐small‐cell lung cancer: A retrospective study. Issue 2 (17th November 2021) - Ishida, Masaki; Morimoto, Kenji; Yamada, Tadaaki; Shiotsu, Shinsuke; Chihara, Yusuke; Yamada, Takahiro; Hiranuma, Osamu; Morimoto, Yoshie; Iwasaku, Masahiro; Tokuda, Shinsaku; Takeda, Takayuki; Takayama, Koichi
Abstract: Background: Chemoimmunotherapy has become a standard treatment option for patients with untreated advanced non‐small‐cell lung cancer (NSCLC). However, numerous patients with advanced NSCLC develop disease progression. Therefore, the selection of second‐line treatment after chemoimmunotherapy is crucial for improving clinical outcomes. Methods: Of 88 enrolled patients with advanced NSCLC who received chemoimmunotherapy, we retrospectively evaluated 33 who received second‐line chemotherapy after progression of chemoimmunotherapy at six centers in Japan. Among them, 18 patients received docetaxel plus ramucirumab and 15 patients received single‐agent chemotherapy. Results: The objective response rate in patients treated with docetaxel plus ramucirumab was significantly higher than that in patients treated with a single‐agent chemotherapy regimen (55.6% vs. 0%, p < 0.001). The median progression‐free survival (PFS) of patients who received docetaxel plus ramucirumab and single‐agent chemotherapy was 5.8 months and 5.0 months, respectively (log‐rank test p = 0.17). In the docetaxel plus ramucirumab regimen group, patients who responded to chemoimmunotherapy for ≥8.8 months had a significantly longer response to docetaxel plus ramucirumab than those who responded for <8.8 months (not reached vs. 4.1 months, log‐rank test p = 0.003). In contrast, in the single‐agent chemotherapy group, there was no significant difference in PFS between the ≥8.8‐ and <8.8‐month PFS groups with chemoimmunotherapy (5.0 vs. 1.6 months, log‐rank test p = 0.66). Conclusion: Our retrospective observations suggest that the group with longer PFS with chemoimmunotherapy might be expected to benefit from docetaxel plus ramucirumab treatment in second‐line settings for patients with advanced NSCLC. Abstract : We investigated the benefit of docetaxel plus ramucirumab as a second‐line therapy after chemoimmunotherapy compared to single‐agent chemotherapy in a real world setting. In second‐line settings, longer PFS with chemoimmunotherapy might be expected to benefit from docetaxel plus ramucirumab treatment for patients with advanced NSCLC.